RESISTANCE TO THE PATRIARCHAL CULTURE IN WHY WOMEN KILL (2019) BY MARC CHERRY - Kamil, Syahrianu Syahidatul; Nurrachman, Dian; Ardiansyah, Erlan Aditya (Saksama: Jurnal Sastra, 2024)
This research aims to contribute to the analysis of feminism related to patriarchal culture and its resistance in the Why Women Kill television series that was released in 2019 and directed by Marc Cherry. The television series Why Women Kill (2019) illustrates that patriarchal culture grows and develops in people's lives as shown by the dominance of men over women in various aspects of society which causes women to experience underdevelopment and limited access to many fields in life. The analysis in this study includes the depiction of patriarchal culture in Why Women Kill (2019) and the resistance to patriarchal culture by female characters in Why Women Kill (2019). In conducting the analysis, the researcher used literary criticism method by using the theory of feminism from the thoughts of Mary Wollstonecraft and Helene Cixous to analyze feminism related to patriarchal culture and its resistance. This research found data analysis of 70 scenes in the film in the form of screenshots and dialogues. This research depicted patriarchy as a culture that is limiting women which makes women backward and disadvantaged, that patriarchy is depicting women as good mothers and wives, depending on men superiority, and as objects to satisfy men desires. In its resistance, women reject the traditional norms by being educated and having dreams and jobs. Women also resist to patriarchy by being independent from role of men, independent in defending themselves, and independent in making life decisions. Women also depicted to rebel against control of men. This research makes an answer to the title of this television series that “why women kill” because they wanted to “kill” norms and cultures that limit and harm women themselves and only fellow women understand how to be in that position. Keyword: Feminism, Film, Patriarchal Culture, Why Women Kill, Women